THE ROLE OF DIGITAL DIPLOMACY AND PROPAGANDA: A DETAILED CASE STUDY OF RUSSIA'S INFLUENCE IN THE 2016 U.S. PRESIDENTIAL ELECTION (Contemporary Journal of Social Science Review, 2025)
This research paper examines Russia's use of digital diplomacy and its parallels to historical propaganda tactics, focusing on its interference in the 2016 U.S. Presidential Election. The paper explores how Russia leveraged digital tools, particularly social media platforms, to shape public opinion, manipulate electoral outcomes, and project power on the global stage. By examining Russia’s use of both digital diplomacy and information warfare tactics, this study highlights the dual use of digital platforms for engagement and manipulation. The paper draws comparisons between traditional propaganda methods, such as state-controlled media, psychological warfare, and modern digital influence campaigns, demonstrating how digital diplomacy in the form of disinformation campaigns has transformed the landscape of international relations. While digital diplomacy offers opportunities for public diplomacy and soft power projection, it also introduces significant ethical challenges, particularly regarding transparency, accountability, and the manipulation of information. The study emphasizes the need for international ethical standards and further research into the implications of digital diplomacy in the digital age.